2019
DOI: 10.1039/c9cp04237g
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the supercapacitive properties of laser deposited graphene-based electrodes through carbon nanotube loading and nitrogen doping

Abstract: Laser-deposited graphene-based electrodes for supercapacitors show significant improvement of capacitance after loading with carbon nanotubes and nitrogen doping. Several electrochemical mechanisms act in the charge storage process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Differently, the hybrid electrodes show softer and curved evolution. Thereby, the equivalent circuit for all the electrodes was represented by a modified Randles cell containing an equivalent series resistor ( R ESR ) originating from the cell constituents, a constant phase element accounting for nonideal capacitance (CPE), a leakage resistor ( R L ) coupled in parallel to the CPE, and a Warburg element attributed to ionic diffusion. , Table S9 presents the equivalent circuit, the equation of CPE impedance, as well as the fitted values of all the passive elements. As observed, the values of R ESR were between 13.3 and 18.6 Ω.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently, the hybrid electrodes show softer and curved evolution. Thereby, the equivalent circuit for all the electrodes was represented by a modified Randles cell containing an equivalent series resistor ( R ESR ) originating from the cell constituents, a constant phase element accounting for nonideal capacitance (CPE), a leakage resistor ( R L ) coupled in parallel to the CPE, and a Warburg element attributed to ionic diffusion. , Table S9 presents the equivalent circuit, the equation of CPE impedance, as well as the fitted values of all the passive elements. As observed, the values of R ESR were between 13.3 and 18.6 Ω.…”
Section: Resultsmentioning
confidence: 99%
“…Not only the composition but also materials morphology (oxides particles size) may influence the electrochemical nature of the devices. For instance, previous works related to the laser synthesis of reduced graphene oxide (rGO)–NiO composite electrodes proved the enhancement of the capacitive (surface) contribution over the diffusive one with the incorporation of NiO nanostructures on the rGO sheets, though this effect is reversed when hundreds of nm NiO clusters are formed revealing the extrinsic pseudocapacitive nature of NiO. , On the other hand, GCD measurements carried out in ca. 10–417 μA/cm 2 current density range revealed maximum capacitances of 25.4 F/cm 3 for NiCe (PVA) at 33.7 μA/cm 2 , about 14.2 F/cm 3 for CeFe (Aq) at 76.6 μA/cm 2 , and 12.1 F/cm 3 at 52.2 μA/cm 2 for NiCe (Aq) devices (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…By adopting the MAPLE methodology, there is a great flexibility in the synthesis of complex compounds and the activation of coupled physical mechanisms between the reactants. In this context, the incorporation of MWCNTs in the targets allowed the deposition of GO-MWCNT-NiO composite films with increased porosity [327]. As…”
Section: Maple For Supercapacitor Electrodesmentioning
confidence: 99%
“…As electrode material, the tendency towards aggregation restricts the surface area of graphene, limiting its capacitance. To separate 2D graphene sheets, carbonaceous pillars (carbon nanotubes, polymers, and carbon polyhedral) are introduced into the graphene composites, which not only inhibits the graphene aggregation, but also contributes to the capacitance [ 32 , 132 , 133 , 134 , 135 ]. Ruan et al reported a “dual-carbon” structure consisting of graphene and microporous carbon polyhedral (NMCP) derived from metal–organic frameworks (denoted as NMCP@rGO, where rGO is reduced graphene oxide) ( Figure 8 a), which benefited from the synergistic effect of dual-carbon and showed superior performance in K-ion hybrid capacitors.…”
Section: Graphene Composites For Post-li Hybrid Capacitorsmentioning
confidence: 99%
“…Carbon materials are widely utilized in the field of energy storage due to their low cost, light weight, and easy recovery. Especially in capacitors, carbon materials function as the various vital constituent parts, such as the activated carbon/porous carbon/graphene for capacitive-type cathodes [ 27 , 28 , 29 , 30 , 31 , 32 ], graphite/graphene/disordered carbon/N-doped carbon nanotubes for battery-type anodes [ 33 , 34 , 35 , 36 , 37 , 38 ], or graphite oxide as a filler for the gel electrolyte [ 39 ]. The capacitor cathode requires the carbon materials to have ample active sites for reversible anion adsorption/desorption.…”
Section: Introductionmentioning
confidence: 99%